2020
DOI: 10.1093/ee/nvaa121
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Male and Female Adults ofCryptolestes ferrugineus(Coleoptera: Laemophloeidae) to Conspecifics With and Without Grain

Abstract: Whether stored-grain insects can communicate with each other inside stored-grain bulks is an important question for the development of pest management programs. Movements of the individual adults of Cryptolestes ferrugineus towards caged adult(s), in the presence or absence of wheat, were studied inside an apparatus (10 cm length), using an infrared camera. The numbers of the caged adults were 1, 20, or 50 of females or males, and 100 or 200 mixed-sex adults. Without grain, both males and females moved towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Moreover, they also observed responses from both sexes to the volatiles in males. Similarly, Currie et al [169] reported that in the absence of air currents and food for feeding, male and female C. ferrugineus were attracted to a single male in an apparatus of 10 cm length; when grain was present, a single male was not enough to attract C. ferrugineus. However, a significant number of females were attracted to 50 males.…”
Section: Chemical Ecology Pheromonesmentioning
confidence: 91%
“…Moreover, they also observed responses from both sexes to the volatiles in males. Similarly, Currie et al [169] reported that in the absence of air currents and food for feeding, male and female C. ferrugineus were attracted to a single male in an apparatus of 10 cm length; when grain was present, a single male was not enough to attract C. ferrugineus. However, a significant number of females were attracted to 50 males.…”
Section: Chemical Ecology Pheromonesmentioning
confidence: 91%